REPRODUCIBILITY OF RADON-IN-WATER MEASUREMENTS BY EMANOMETRY TECHNIQUE. Issue 2 (31st October 2020) - Di Carlo, C; Venoso, G; Lepore, L; Ampollini, M; Carpentieri, C; Antignani, S; Caprio, M; Remetti, R; Bochicchio, F
Abstract: The emanometry test method is one of the detection techniques of radon in water satisfying requirements of Directive 2013/51/Euratom with regards to the detection limit. Quality assurance (QA) procedures were developed and implemented for a measuring system relying on such a technique. These procedures mainly address the following: (i) the assembling of each component of the degassing circuit, (ii) the sample transfer from the transport container to the degassing vessel and (iii) the control of all the influencing quantities. Three identical measuring systems have been used to analyse in parallel 39 water samples with the aim to evaluate the effectiveness of QA procedures in terms of reproducibility. The results showed quite low variability (<15% for the 84% of measurements in the range 10–100 Bq L −1 ) among the three different measuring systems.